Computational Characterization of Astrophysical Species: The Case of Noble Gas Hydride Cations - Montes de Oca-Estévez, María Judit; Prosmiti, Rita (Frontiers in Chemistry, 2021)
Theoretical–computational studies together with recent astronomical observations have shown that under extreme conditions in the interstellar medium (ISM), complexes of noble gases may be formed. Such observations have generated a wide range of possibilities. In order to identify new species containing such atoms, the present study gathers spectroscopic data for noble gas hydride cations, NgH+ (Ng = He, Ne, Ar) from high-level ab initio quantum chemistry computations, aiming to contribute in understanding the chemical bonding and electron sharing in these systems. The interaction potentials are obtained from CCSD(T)/CBS and MRCI+Q calculations using large basis sets, and then employed to compute vibrational levels and molecular spectroscopic constants for all known stable isotopologues of ground state NgH+ cations. Comparisons with previously reported values available are discussed, indicating that the present data could serve as a benchmark for future studies on these systems and on higher-order cationic noble gas hydrides of astrophysical interest.